Die strafrechtliche Verantwortlichkeit für Kartellrechtsverstöße nach dem Recht der Westafrikanischen Wirtschafts- und Währungsunion (UEMOA) Ein gelungenes Rechtstransplantat aus dem Recht der Europäischen Union? - N'Toumon, N'Kouano Anasthasie (Schriften zum Internationalen und Europäischen Strafrecht, 2021)
The study deals with the antitrust sanctions of the West African Economic and Monetary Union (Union Economique et Monétaire Ouest Africaine - UEMOA) and its member states, which was taken from EU law as a legal transplant. Differences to EU law are elaborated and, in particular, areas are identified in which UEMOA-specific problems require a different interpretation of sanctions law in the interest of effective protection of competition. In addition, the difficulties of implementation are highlighted and far-reaching and comprehensive measures are proposed, oriented towards European antitrust sanctions law, in order to achieve a more efficient prosecution of antitrust violations.